Brand‐to‐generic levetiracetam switching: a 4‐year prospective observational real‐life study. (1st February 2018) - Trimboli, M.; Russo, E.; Mumoli, L.; Tripepi, G.; Fortunato, F.; Mastroianni, G.; Abate, F.; De Sarro, G.; Gambardella, A.; Labate, A.
Abstract : Background and purpose: The purpose of this study was to determine whether switching from branded levetiracetam (Keppra ® ) to a levetiracetam generic equivalent product (Matever ® ) in an epilepsy cohort could provide adequate results in terms of seizure control and tolerability. Methods: To be eligible for the study, patients had to have been taking Keppra ® as monotherapy or polytherapy for at least 6 months. Between March 2013 and April 2017, patients were invited to switch to Matever ® as part of their follow‐up. We evaluated the number of seizures per month, drug‐related adverse events and electroencephalography before the switch (T0, baseline) and 6 months after switching (T1). Furthermore, we reported the long‐term follow‐up of patients who continued to use Matever ® after the end of the study, considering the most recent visit for each patient (T2). Results: A total of 55 patients refused the switch. Among the remaining 125 patients, 59 (47%) were treated using Keppra ® as monotherapy and 66 (53%) were on Keppra ® as polytherapy. All 125 patients were subjected to switching from Keppra ® to Matever ® . Comparing patients before (T0) and after (T1) switching, we found no statistically significant differences in terms of seizure frequency and occurrence of adverse effects. There were no significant differences (number of seizures/month and drug‐related adverse events) between patients treated with Matever ® as monotherapy and patients who refused the switch and continued to use Keppra ® as monotherapy for a long‐term follow‐up of 48 months. Electroencephalography findings were also unchanged. Conclusion: In our sample, brand‐to‐generic levetiracetam switching was effective and safe in both monotherapy and polytherapy regardless of the epilepsy syndrome.